Effect of Maltodextrin Concentration on Anthocyanin Content and Antioxidant Activity of Rukem Fruits Extract Powder - Lydia Ninan Lestario; Melanie Melanie; Monika Rahardjo (Jurnal Teknologi dan Industri Pangan, 2023)
Rukem (Flacourtia rukam Zoll. & Mor.) is an Indonesian tropical fruit with purple peel indicating anthocyanin content; therefore, the fruit can be a potential source of natural colorant. However, anthocyanins are commonly unstable and reactive towards temperature, light, and oxygen. For this reason, encapsulation process is an attempt to improve its stability. The aim of this research was to determine the most efficient concentration of maltodextrin to coat the anthocyanins in rukem fruit, considering the total anthocyanin and antioxidant activity. The fruit was extracted with several concentrations of citric acid 0.5, 1, 2, 3, 4, 5 % (b/v), and the optimal concentration was used to extract anthocyanin. The extract was then mixed with maltodextrin at following concentrations: 40, 50, 60, 70, and 80% (w/v). The mixture was homogenized, then spray-dried with spray dryer Lab Plant SD-05, Keison, UK. The dried samples were analyzed for chemical (moisture, ash, pH, anthocyanin, antioxidant activity) and color (L*, a*, b*) properties. The results showed that 5% citric acid and 40% maltodextrin (w/v) gave the most efficient yield of extraction, and the best effects on anthocyanins powder, resulting in the highest antioxidant activity (74.28± 0.41%), total anthocyanins (3.96±0.08 mg/100 g), encapsulation efficiency (19.26±0.41%) and color values of L* 87.46±0.07; a* 16.21±0.09, and b* -1.60±0.02.